Developing Transdisciplinary-based Material Design for Akidah Akhlak Learning - Lusinta Rehna Ginting; Saiful Akhyar Lubis; Rusydi Ananda (Dinamika Ilmu, 2022)
Transdisciplinary-based learning (TDBL) is a need of teachers in teaching where its existence offers for solutions to solve teaching and learning problems in class. In this case, the presence of TDBL in Aqidah Akhlak subject means integrating Islamic teaching into science as knowledge in a holistic way. Thus, this study aims to propose a new way of teaching by developing the learning materials for the Aqidah Akhlak subject which is integrated into TDBL. Plomp’s model of research and development design is used in this research which typically includes five stages including problem analysis, design, realization, implementation, and evaluation. The result from expert validation both for student and teacher books is considered in the eligible category, highly eligible for field trial assessment, and practical category for the practical assessment. Students’ performance on Aqidah Akhlak subject is dominated by moderate level rather than high one. T-test proved that the use of TDBL Aqidah Akhlak learning materials effective to be utilized in class. Through the result of the study, it can be concluded that the proposed product of TDBL Aqidah Akhlak learning materials can be used both for students and teachers. Discussion and research implications are discussed further in this study.